Fortran algorithm for monitoring leachates and interpreting physico-chemical data of contaminants in ground water (2012)
A FOTRAN 90 algorithm was developed to interpret leachate geochemical data of polluted ground water in Lagos, based on 19 selected physico-chemical parameters adopted by the United States Geological and Environmental Survey Agency in compliance with the World Health Organization (WHO) prescribed standards for safe water consumption. By applying the Fortran program, the portability of leachates contaminated water were ascertained in compliance with WHO requirements.